Sustainability à la carte: A systematic review of green restaurant research (2010-2023) - Yong, Rachel Yuen May; Chua, Bee-Lia; Fakfare, Pipatpong; Han, Heesup (Routledge, 2024)
This paper delves into the realm of green restaurants, which seamlessly combine environmentally conscious practices with culinary excellence. It scrutinized 106 reputable hospitality and tourism articles using systematic literature review methods. The analysis, featuring descriptive examination and topic modeling, revealed significant developments in green restaurant research and highlighted their potential to address sustainability challenges. Employing an adapted TCCM framework (Theory, Context, Characteristics, and Methodology), the review suggests new research directions, placing a heightened focus on the “characteristics” aspect to align academic insights with global priorities and industry requirements. This promotes actionable and collaborative strategies for eco-friendly restaurants. © 2023 Informa UK Limited, trading as Taylor & Francis Group.